Needed More Than Ever: Internationalization of Medical Education - Wu, Anette; Noel, Geoffroy P. J. C.; Leask, Betty; Unangst, Lisa; Choi, Edward; de Wit, Hans (International Higher Education, 2020)
How has internationalization translated to the sphere of medical education? This article considers that question in the US context, pointing to the distinct, yet overlapping, concepts of global health and internationalization of medical curricula, and advocating for an interdisciplinary approach. Failure to incorporate internationalization into medical education will limit medical students’ understanding of the global, social, cultural, and ethical issues associated with medical practice and research, with implications for the current pandemic and beyond.